Digitalisasi Saluran Distribusi Dengan Pendekatan AI untuk Optimalisasi Penjualan Produk Olahan Komunitas Perikanan dan Usaha Wanita Lyvia Nusa Boga - Kolondam, Arifmanuel; Wangarry, Andreas Randy; Lambonan, Oldi M; Purba, Ficky (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
With increasingly fierce business competition, MSMEs are required to be able to increase sales optimally. One factor that greatly influences this achievement is the selection and management of distribution channels. Problems that often arise in distribution practices are the mismatch between market needs and the distribution system implemented. Lyvia products are viewed from a business perspective, they have enormous potential in the industry, however, marketing strategies that still rely on conventional marketing have resulted in insignificant market share growth. Therefore, optimizing distribution channels by utilizing digital technology is an urgency that must be done to expand the market coverage of Lyvia products. The method of implementing this Community Service stage is carried out through five interconnected stages, namely the socialization stage, training, technology application, mentoring and evaluation, and program sustainability. These socialization, design and training mentoring activities can be concluded that there is a need to show a significant need among MSMEs regarding the digitalization of website-based distribution channels, which can help in increasing product sales and can reach consumers throughout Indonesia so they can easily purchase processed products from Lyvia Nusa Boga. There was high enthusiasm from the owners and employees of Lyvia Nusa Boga to improve their understanding and skills in operating the website, as well as their understanding of the website's user flow and features. This community service activity, involving lecturers and students as a team, successfully reached its target audience, including the owners and employees of Lyvia Nusa Boga. It was implemented comprehensively through preparation, implementation, and evaluation.